Assessment of Financial Performance and Competitive Dynamics of Insurance Companies on the Indonesian Stock Exchange - Syazwan Hassan (Indonesia Accounting Research Journal, 2023)
This research presents a comprehensive analysis of the financial performance of insurance companies listed on the Indonesian Stock Exchange. The study evaluates the fiscal health, operational efficiency, and competitive standing of these insurers by examining various financial metrics. The analysis encompasses a diverse spectrum of companies, revealing trends in premium growth, profitability, underwriting efficiency, and solvency ratios. Key findings highlight a market marked by a consistent increase in premiums underwritten, reflecting a growing demand for insurance products within the Indonesian market. Additionally, the research uncovers a variance in the profitability and efficiency of underwriting practices among insurers, showcasing a range of successful models and areas necessitating improvement. These insights have significant implications for industry practitioners, regulators, investors, and policymakers. They provide a roadmap for refining operational strategies, enhancing risk management practices, and optimizing financial performance. The study's findings serve as benchmarks for industry best practices and offer recommendations for the improvement of underperforming entities. This research not only contributes to an understanding of the financial health and competitive landscape of Indonesian insurance companies but also guides strategic decision-making, regulatory adaptations, and investments, fostering a more stable and competitive insurance sector within the Indonesian market.